Pengaruh Leverage, Kualitas Audit, dan Ukuran Perusahaan Terhadap Kualitas Laporan Keuangan: Studi pada Perusahaan Sektor Industri yang Terdaftar di Indeks Saham Syariah Indonesia Periode 2020-2024 - Nurul Umiah; Mohammad Orinaldi; Laily Ifazah (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to examine the simultaneous and partial effects of Leverage, Audit Quality, and Firm Size on the Quality of Financial Statements in industrial sector companies listed in the Indonesia Sharia Stock Index (ISSI) for the 2020–2024 period. This research uses secondary data. The sample consists of 15 companies out of 42, selected using the Purposive Sampling technique. The method applied in this study is descriptive quantitative. The data analysis techniques include descriptive statistics, panel data regression analysis, classical assumption tests, and hypothesis testing. The results show that partially, the t-test results indicate that Leverage, Audit Quality, and Firm Size have a significant effect on the Quality of Financial Statements. This is evidenced by the probability value of each variable being <0.05, indicating that all three independent variables significantly influence financial statement quality. The F-test results also reveal that Leverage, Audit Quality, and Firm Size collectively have a significant effect on the Quality of Financial Statements. This is supported by the calculated F-value being greater than the F-table, with a significance value of 0.0000 < 0.05, and a coefficient of determination (R²) of 69.8835%. The findings further indicate that Audit Quality has the strongest influence on the quality of financial statements. This implies that companies need to select competent and independent auditors to ensure transparency and accountability in financial reporting